Extrinsic and intrinsic factors acting as barriers or facilitators in nurses’ implementation of clinical practice guidelines: a mixed-method systematic review: Nurses’ implementation of guidelines. - Gallione, Chiara; Barisone, Michela; Molon, Antonella; Pavani, Moreno; Torgano, Cristina; Bassi, Erika; Dal Molin, Alberto (Acta Biomedica Atenei Parmensis, 2022)
Background and aim of the work: Greater evaluations are needed to identify barriers or facilitators in nurses’ guidelines adherence. The current review aims to explore extrinsic and intrinsic factors impacting nurses’ compliance.Methods: Mixed-method systematic review with a convergent approach, following the PRISMA checklist and the JBI Mixed Methods Review Methodological Guidance was conducted. MEDLINE, Embase, CINAHL were systematically searched, to find studies published between 2010 and 2021, including qualitative, quantitative or mixed-methods articles.Results: Sixty studies were included, and the major findings were analysed by aggregating them in two main themes: intrinsic and extrinsic factors. The intrinsic factors were: a) knowledge and skills; b) attitudes of health personnel; c) sense of belonging towards guidelines. The extrinsic factors were: a) organizational and environmental factors; b) workload; c) guidelines structure; d) patients and caregivers’ attitude.Conclusions: The included studies report lack of resources, among environmental factors, as the main barrier perceived. Nurses, who are at the forefront in addressing the direct application of knowledge and skills to ensure patient safety, have a higher perception of this kind of barriers than other healthcare personnel. Potential facilitators emerged in the review are positive feedback and reinforcements at the workplace, either from the members of the team or from the leaders. Moreover, the level of active participation of the patient and caregiver could have a positive impact on nurses’ guidelines adherence. Guidelines implementation remains a complex process, resulting in a strong recommendation to support health policymakers and nursing leaders in implementing continuing education programs.